Meningkatkan kewaspadaan masyarakat terhadap Covid-19 pada masa PPKM di Kelurahan Cibodasari - Dabella Yunia; Nada Shafa Soraya Gandakusumah; Nina Safitri Zahra; Musdalifah; Farlina Fajrianti; Haikal Diarahmana Putra; Firhani Ashri; Itta Qunnisa (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
The Covid-19 pandemic has hit Indonesia since March 2020 until now. All components of the Indonesian state must unite to overcome the pandemic. One of the tangible forms of community service from Sultan Ageng Tirtayasa University is to increase public awareness of Covid-19 during the Enforcement of Restrictions on Community Activities in Cibodasari Village. Community service activities carried out include socializing covid-19, spraying disinfectants, and socializing the Enforcement of Restrictions on Community Activities. The activity was carried out in a hybrid manner by implementing a strict health protocol. The result of the implementation of these activities is that the residents of the Cibodasari sub-district are increasingly aware of Covid-19 so that the discipline in applying health protocols is felt, the wider impact is felt at the Tangerang City level by decreasing the level of the Bed Occupancy Ratio.